2022
DOI: 10.2340/jrm.v54.573
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal Muscle Changes in the First Three Months of Stroke Recovery: A Systematic Review

Abstract: Background: Rehabilitation is important in the first months after a stroke for recovery of functional ability, but it is also challenging, since distinct recovery trajectories are seen. Therefore, studying the early changes in muscle characteristics over time (e.g. muscle strength, muscle mass and muscle volume), which are known to be associated with functional abilities, may deepen our understanding of underlying recovery mechanisms of stroke survivors.Objective: This systematic review aims to describe the lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 73 publications
(211 reference statements)
0
6
0
Order By: Relevance
“…Nutritional interventions can reduce the risk and improve the prognosis of these diseases [97][98][99]193,[232][233][234][235][236][237]. Although a consensus on nutritional management for sarcopenia and frailty has not been established, numerous studies have been conducted on this topic in recent years, as shown in Figure 2 [18][19][20][21][22][23][24][25][26][27][28][29][30][94][95][96]121,124,[126][127][128][129]164,165,222,223,226]. The need for oral nutritional supplements to reduce sarcopenia and frailty [53,[73][74][75][76][77][78] is still controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Nutritional interventions can reduce the risk and improve the prognosis of these diseases [97][98][99]193,[232][233][234][235][236][237]. Although a consensus on nutritional management for sarcopenia and frailty has not been established, numerous studies have been conducted on this topic in recent years, as shown in Figure 2 [18][19][20][21][22][23][24][25][26][27][28][29][30][94][95][96]121,124,[126][127][128][129]164,165,222,223,226]. The need for oral nutritional supplements to reduce sarcopenia and frailty [53,[73][74][75][76][77][78] is still controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in muscle architecture can take place as early as 3 weeks after stroke [ 39 ]. Muscle thickness decreases in the first months of recovery [ 40 ], whereas the evolution to the chronic stage leads to increased muscle tone and stiffness. This has been shown in the upper [ 41 , 42 ] and lower [ 36 , 38 ] limb in chronic stroke survivors.…”
Section: Discussionmentioning
confidence: 99%
“…In this review, we provide an overview of the literatures to determine whether nutrient deficiencies relate to the risk of diseases and whether nutrient intake can prevent the onset of diseases or enhance treatment outcomes (Figure 3). Malnutrition and nutrient deficiencies have been associated with an increased risk of CKD [90][91][92][93], stroke [158][159][160], osteoporosis [196,197], fractures Although a consensus on nutritional management for sarcopenia and frailty has not been established, numerous studies have been conducted on this topic in recent years, as shown in Figure 2 [18-30,42-78, [94][95][96]122,125,[127][128][129][130]165,166,225,226,229]. The need for oral nutritional supplements to reduce sarcopenia and frailty [53,[73][74][75][76][77][78]] is still controversial.…”
Section: Discussionmentioning
confidence: 99%